Progressivism In Language Learning: Application of The Educational Philosophy In Language Competence Development - Kamal, Sirajuddin; Jumadi, Jumadi; Listia, Rina (CAKRAWALA LINGUISTA, 2025)
ABSTRACTThe implementation of progressive educational philosophy in language education in Indonesia represents not only a pedagogical shift but also a transformative approach to modernizing the national education system. Rooted in John Dewey’s principles of experiential learning, contextual relevance, and social collaboration, progressive education aligns with the demands of 21st-century language learning. This study delves deeper into its application, revealing significant advancements in students’ linguistic competence, with writing and speaking skills increasing by up to 24% and 20%, respectively. Furthermore, progressive methods such as project-based learning, simulations, and the integration of technology have fostered critical thinking, creativity, and collaboration, with 95% of students reporting higher engagement in gamified learning environments. Beyond its immediate impacts, progressive education in language learning equips students with the tools to navigate global challenges and become active contributors to their communities. Despite its promise, barriers such as infrastructural limitations, insufficient teacher readiness, and systemic resistance highlight the need for targeted interventions. This study concludes that progressive education offers a pathway to holistic transformation in Indonesia’s language education, advocating for policy reforms, investment in technology, and comprehensive teacher training to institutionalize its benefits on a national scale.